GERAKAN LITERASI NUMERASI CERIA UNTUK MENUMBUHKAN MINAT BACA DAN KEMAMPUAN MATEMATIKA DASAR ANAK USIA DINI - Sri Irawati; Ema Surahmi; Devie Reztia Anjarani; Arju Hidayatullah; Firda Aulia Nabila (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2026)
Literacy and numeracy are fundamental competencies that should be developed from an early age to support children’s cognitive, language, and logical thinking development. This community service activity aimed to foster reading interest and strengthen basic numeracy skills in early childhood through the Cheerful Numeracy Literacy Movement. The program was implemented at PAUD Az-Zahrah and RA Muslimat NU VII Pademawu, Pamekasan by providing a literacy–numeracy reading corner, conducting sharing sessions with teachers and parents, and introducing creative literacy–numeracy learning media. The reading corner was equipped with child-friendly materials such as picture books, educational fairy tales, children’s encyclopedias, and story-based mathematics books. Evaluation using questionnaires showed very positive responses, with mean scores of 3.37-3.62 on a four-point scale. Although long-term assistance and monitoring have not been optimally implemented, this program demonstrates strong potential as an initial model for strengthening early childhood literacy and numeracy through collaborative and creative learning environments.